Design, Synthesis, and Evaluation of Orally Available Clioquinol-Moracin M Hybrids as Multitarget-Directed Ligands for Cognitive Improvement in a Rat Model of Neurodegeneration in Alzheimer’s Disease - Wang, Zhiren; Wang, Yali; Wang, Bo; Li, Wenrui; Huang, Ling; Li, Xingshu (Journal of medicinal chemistry, 2015)
A novel series of clioquinol-moracin hybrids were designed and synthesized by fusing the pharmacophores of clioquinol and moracin M, and their activities as multitarget-directed ligands against Alzheimer’s disease were evaluated. Biological activity results demonstrated that these hybrids possessed significant inhibitory activities against phosphodiesterase 4D (PDE4D) and Aβ aggregation as well as remarkable antioxidant effects and excellent blood–brain barrier permeability. The optimal compound, 18d (WBQ5187), exhibited excellent PDE4D inhibitory potency (IC50 = 0.32 μM), significant antioxidant effects, appropriate biometal chelating functions, and interesting properties that modulated self- and metal-induced Aβ aggregation. Two-dimensional NMR studies revealed that 18d had significant interactions with Aβ1–42 at the R5, H6, H14, Q15, and F20 residues. Furthermore, this typical hybrid possessed preeminent neuroprotective effects against inflammation in microglial cells. Most importantly, oral administration of 18d·HCl demonstrated marked improvements in cognitive and spatial memory in a rat model of Alzheimer’s disease and protected hippocampal neurons from necrosis.